REPOSISI TINGKAT KEHARAMAN RIBÂ BAGI TERWUJUDNYA KEADILAN EKONOMI DALAM PERSPEKTIF AL-QUR’AN DAN HADIS NABI SAW - Andi Rosa (Holistic al-Hadis, 2015)
The research question to be dealt with here is, what factors cause Bank interests of conventional Banks regarded as harâm from the perspective of Islam? I conducted the method of Semantic exegesis which relates to the topic, i.e. economics. The interest system of modern economics, according to al-Qur’an and prophetic traditions, can be regarded as harâm in a condition that there is no contentment (ridlâ) in any of both sides (the Bank or the creditors), neither in direct way (i.e. the creditor does not comprehend the risk) nor in indirect way (i.e. the creditor absolutely in need of the loan). In contrary, if any of both sides has to bear the risk, the interest system will be regarded to as harâm. Findings of this research show that the interest system in conventional Banks, in particular levels, does not reflect values of economic fairness. This applies when a creditor of small businesses does not have access to currency exchange system. On this basis, there should be global currency system for Islamic states or other particular states with a wide range of Muslim population, as like Euro for European and Dollar for the US. Further, the research proposes the collaboration of alms (zakât) with banking systems. The significance of these systems find it context in realizing inclusive and independent economic systems, to be the implementation of of values of economic fairness.